The MELD score predicts the short-term and overall survival after liver transplantation in patients with primary sclerosing cholangitis or autoimmune liver diseases - Hoffmann, Katrin; Hinz, Ulf; Ganten, Tom M.; Gotthardt, Daniel; Longerich, Thomas; Schirmacher, Peter; Schemmer, Peter (Langenbeck's archives of surgery, 2014)
Purpose: Liver transplantation (LT) is well established in patients with autoimmune liver disease. Despite excellent outcomes, organ scarcity demands careful patients’ selection and timing of transplantation. Methods: This retrospective study analyzes data of 79 consecutive patients with primary sclerosing cholangitis (PSC), autoimmune hepatitis (AIH), and overlap syndrome, undergoing LT between 2001 and 2012. Overall survival (OS) and graft survival were assessed using Kaplan-Meier estimate. Multivariate survival analysis was performed to identify prognostic factors by using Cox regression model. Results: After 59.6-month median follow-up, the 5-year OS and graft survival were 75.3 and 68.8 %, respectively. The 5-year survival rates for patients with PSC (n = 57), AIH (n = 17), and overlap syndrome (n = 5) were 76.3, 76.0, and 60.0 %. The 90-day mortality rate of 70.0 % was significantly higher in patients with a labMELD score ≥20 (n = 10) compared to 26.1 % in 69 patients with a labMELD <20 (p = 0.009). A lab Model for End-Stage Liver Disease (MELD) score ≥20 was an independent predictor of impaired OS (p = 0.050, hazard ratio 2.5). The 5-year OS was 55.7 % in patients with a labMELD score ≥20 compared to 84.7 % in patients with a labMELD score <20.Conclusion: The recipients’ MELD score is a predictor for the short-term outcome after LT in patients with autoimmune liver disease. Meticulous selection for transplant listing remains necessary to safe scarce donor organs.